Diurnal attraction of fruit flies (Diptera: Tephritidae) to methyl eugenol in a village ecosystem in Tanjung Bungah, Penang, Malaysia - Wee, Suk Ling; Hee, Alvin Kah Wei (Faculty of Science and Technology, Universiti Kebangsaan Malaysia, 2018)
Diurnal rhythm of male Bactrocera fruit fly attraction to methyl eugenol (ME) was investigated using clear traps design in a village ecosystem in Tanjung Bungah, Penang, Malaysia. The diurnal rhythm pattern studied by half-hourly sampling from 07:00 to 18:00 hr showed significant male fruit fly attraction to ME in the morning from 07:30 to 09:30 hr, with a distinct peak at 08:30-09:00 hr. The male attraction to ME was significantly lower in the afternoon and remained low approaching late afternoon. The ME-responding fruit fly species captured were B. dorsalis (86%), which dominated the local Bactrocera community, followed by B. umbrosa (5.8%) and B. carambolae (0.1%). This showed that B. dorsalis is a more dominant species than its sibling species, B. carambolae in the area studied. In addition, ca. 8.1% of Bactrocera male flies that bore intermediate morphological characteristics between B. dorsalis and B. carambolae were also captured in those traps. The present study shows that for ME-responding Bactrocera spp., male attraction to ME occurs throughout the day with peak period of attraction to ME occurring ca. 30 mins following sunrise for 2 hrs before gradually tapering off.